Implementation of Sentiment Analysis and Social Network Analysis of Twitter User Opinions on Web-Based Political Issues - Muharram, Syair; Ahyar, Muh.; Asriyadi, Asriyadi (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
The functionality of both sentiment analysis and social network analysis on social media such as Twitter or X can holds significant potential for understanding public opinion, especially in political-related issues. Despite its potential, there is currently lack of application that can provide these types of analyses. This research aimed to help to analyse public opinion in the field of political issues by using sentiment analysis and social network analysis techniques that can help to analyse the tendency of public opinion polarity on Twitter or X social media and to visualize the relationship of social media accounts with other social media accounts. The results obtained from this research are web applications that can help in problems related to sentiment analysis and network analysis using libraries from the Python programming language, and NodeJs. Based on the results of blackbox testing and technical testing, it can be concluded that the system that has been built can run in accordance with the predetermined design.